Utilization of Augmented Reality Technology on Android-based Fashion Catalog Application - Kuncorojati, Fariz Wahyu; Wibowo, Adityo Permana (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
Fashion is a primary need for society, especially teenagers. One way to look attractive is to wear clothes that follow the trend. Many clothing stores compete with certain promotional methods. Many strategies are used to promote products fashion one way is through the catalog. View catalog fashion presented in the form of print media may be commonly used in stores to describe products fashion to consumers. The purpose of this study is to generate applications that can be used to find out product models in detail by utilizing technology augmented reality. The observation method was carried out by collecting fashion product data from several fashion stores such as Erigo Store and Uniqlo CO. -The literature study approach is used by gathering information from various journals and papers from Google Scholar. With the Android-based application system using technology augmented reality as a promotional media for clothing sales, it can facilitate fashion products promotion for the stores and make it simpler for prospective customers to identify models and motifs and see the 3-dimensional shape of clothing products without needing to visit the retailer. From the outcomes of the black box testing that has been performed, the fashion catalog application uses augmented reality, is free from functional errors and is able to display all 3D objects of the product fashion which is already stored in the Vuforia database.